Pengaruh Pendampingan Orang Tua Terhadap Proses Pembelajaran Anak Pada Masa Pandemi Covid-19 - Ainol; Yulianti, Nafisah Eka (At- Ta'lim : Jurnal Pendidikan, 2023)
This study aims to determine the correlation between parental assistance and the learning process during the Covid-19 period. The approach used in this study is a quantitative approach, namely collecting data in the form of numbers or qualitative data which is quantified using statistical analysis. The data collection method uses a Likert scale model questionnaire instrument, which reveals the attitudes and perceptions of a person or several people about learning phenomena in the form of a questionnaire. This questionnaire was given to 57 respondents to obtain valid data regarding parental assistance and children's online learning processes during the Covid 19 pandemic. The results of this study concluded that there was a positive influence of parental assistance on children's learning processes at MTs. Dlaaul Islam can be seen from the results of simple linear regression analysis Y = a + bx (72.77 = 2.78 + 0.93 x 75). So if parental assistance is increased by 1 point, the child's learning process will increase by 2.78%. From the R Square value, it shows that the contribution of 0.71 (71%) of the child's learning variable can be estimated by the variable of parental assistance, while the remaining 29% is influenced by other factors not examined